Preparation and Evaluation of Chitosan Microcapsules of Metronidazole using Tripolyphosphate Cross-linking Method - Garud, Akanksha; Garud, Navneet (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Metronidazole microcapsules with a coat consisting of alginate and the natural cationic polymer, chitosan were formulated by using tripolyphosphate cross-linking method and were investigated with a view to develop mucoadhesive microcapsules. The microcapsules were evaluated for their surface morphology, microencapsulation efficiency, in-vitro wash-off test, swelling behavior and in-vitro drug release. The microcapsules formed had rough surface morphology in scanning electron microscopy. The drug entrapment efficiency was found to be in the range 75.2±1.31% and 82.1±0.75%. Chitosan microcapsules displayed a limited amount of swelling which is supposed to be related to the degree of cross-linking with tripolyphosphate. The microcapsules showed better mucoadhesive property at intestinal pH 7.4 than at gastric pH 1.2 in the in-vitro wash-off test. The drug release was found to be slow and extended over long duration of time. Key words: Metronidazole microcapsules; chitosan; mucoadhesion; tripolyphosphate DOI: http://dx.doi.org/10.3329/dujps.v9i2.7897 Dhaka Univ. J. Pharm. Sci. 9(2): 125-130, 2010 (December)